Computational vision and medical image processing : VipIMAGE 2007 : proceedings of Vipimage 2007 - Firstveccomas thematic conference on computational vision and medical image processing, Porto, portugal, 17-19 October 2007 - Conference on computational vision and medical image procesing (1st : 2007 : Porto, Portugal); Travers, Joao Manuel R. S.; Jorge, R. M. Natal (London : Taylor & Francis, 2008)
40